Hódmezővásárhely és környékének feltérképezője és leírója - Gálné Horváth, Ildikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
Bodnar, Bela name only on Hodmezovasarhely for living persons known, little figure in an encyclopedia his name, the city’s inhabitants commemorate him with respect however. Two of his works appeared, in which collected the expressions attaching to the city’s geography, names, natural form ations in an alphabetical order. He started discovering surroundings at his age of 12 and gathered diligently geographical names attaching to the city, lost surface ones outside and inner-city area from aged people. Unfortunately his works is publishing in many manuscripts was left over, altogether only a book appeared in his form after his death. His research results mean a starting point to a number area of science in our days, let it be nature or society geography, ethnography, religion geography, history, linguistics.